Implementation of the TBM Rumah Asa Program as a Form of Creative-Innovative Education Based on Entrepreneurship and Local Wisdom in Yogyakarta City - Wahyuni, Rita Nur; Fauziah, Puji Yanti; Aisyah, Siti; Al-Fayed, Muhammad Yusuf (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
Implementation of Rumah Asa's TBM (Taman Bacaan Masyarakat) Program is an effort to encourage creative education based on entrepreneurship and local wisdom in Karangkajen Village, Brontokusuman, Yogyakarta City. Through innovative and creative approaches, this program aims to provide wider access to education for the community. The Rumah Asa TBM program combines education and local wisdom as the main foundation. In this program, education focuses on academic aspects and developing creative and entrepreneurial skills that can help students develop their potential holistically. This study uses a descriptive qualitative research method using an in-depth and comprehensive sustainable development perspective (sustainable development). The research instruments used for data collection were field observations, interviews, and documentation. Data were analyzed using Miles and Huberman's interactive model, starting from data collection, reduction, presentation, and conclusion. The results of the study show that by combining approaches to creative education, entrepreneurship, and local wisdom, the Rumah Asa TBM program has the potential to provide sustainable benefits for students and the surrounding community, including (1) Increasing access to experience-based learning: (2) Creative education for deeper understanding and creative problem solving; (3) Skill-based entrepreneurial empowerment; (4) Utilization of local wisdom as a source of knowledge; (5) Literacy-based sustainable community development.